CAPACITY AND COP ANALYSIS OF DOUBLE EFFECT STEAM ABSORPTION CHILLERS USING ZERO ORDER MODEL - CHOY, JAN FUNG (2018)
Steam absorption chillers produced chilled water using the steam generated from heat recovery steam generator (HRSG). Most of the chillers are double effect cycle absorption chillers. The double effect chillers have COP in the range of 1.0 to 1.2. This study is on the capacity and coefficient of performance (COP) of double effect water-lithium bromide steam absorption chiller at a district cooling plant. The performance of the real absorption cycle will always less than the ideal reversible cycle due to some irreversibility process such as heat transfer between absorption cycle and surrounding. A better method that considers the factor of irreversibility should be used in order to produce an accurate prediction of performance trends. The main objective of this study is to evaluate COP of water-lithium bromide absorption chiller using zero order model through actual data that acquired from gas district cooling (GDC) UTP plants. Reversible and zero order model were used in this study as comparison. Results indicated that both reversible and zero order model had a higher COP value than actual COP calculated, but zero order model showed a better accuracy compared to reversible model. The data retrieved from the operations had been analyzed to further improve the performance of absorption chillers technology in the future.